Numerical and experimental analyses of modal frequency and damping in tow-steered CFRP laminates. (15th July 2020) - Pereira, D.A.; Guimarães, T.A.M.; Resende, H.B.; Rade, D.A.
Abstract: This present paper is devoted to the numerical and experimental investigation of the modal characteristics of composite laminates, with emphasis on damping. Complementing previous studies dedicated to conventional laminates, one considers variable-angle tow laminates, in which the fibers are deposited following curvilinear trajectories. The main objective is to characterize the influence of fiber steering on the damping levels, and evaluate the possibility of achieving increased damping. A dynamic model is derived by combining the semi-analytical Rayleigh-Ritz approach, the Classical Lamination Theory, and the Strain Energy Method. This later enables to estimate the specific damping capacity of each vibration mode. Based on this model, analytical developments are performed aiming at putting in evidence the contribution of each strain component in each layer of the laminate to the specific damping capacities. The results of numerical simulations are presented, enabling to compare the values of specific damping capacities and vibration natural frequencies obtained for variable-angle tow and conventional laminates in a variety of simulation scenarios. Some of the numerical results are validated by comparisons with experimental counterparts. The results confirm the effectiveness of design strategies intended to regulate and possibly increase the damping levels of composite laminates by exploring fiber steering.